The role of perceived attributions in predicting Facebook status updates. - Tan, Hui Ting. (2010)
The increased use of social networking sites like Facebook allows users to conveniently form online supporting relationships with each other. Six hypotheses in this study explored how the perceived locus and controllability of the cause of an event may influence a new form of online supporting relationship – posting and responding to status updates. Results showed that perceived locus and controllability did not predict the likelihood of posting negative nor positive events on one’s status update on Facebook. It also did not predict the likelihood of responding to a status update about a negative event. Perceived locus and controllability were however able to predict the likelihood of responding to a status update about a positive event.